Qualitative and morphological evaluation of the mandibular bone using computed tomography - Smita R Priyadarshini; Pradyumna K Sahoo; Shayari Niyogi; Swati Patnaik; Sanat K Bhuyan (Wolters Kluwer Medknow Publications, 2020)
Context: Determining the amount of cortical and cancellous bone present in the mandible is an important criterion for the selection of proper implant size and reduction of post implant placement complications. It becomes difficult to manage the presence of lingual undercuts when there is perforation of either the buccal or lingual cortical plates. Computed tomography (CT) images of the mandible can reduce the risk of complications by evaluating the thickness of cortical and cancellous bone in the mandible. Aims: Evaluate thickness of the buccal and lingual cortical plates and cancellous bone. Gender variation in the cancellous bone and cortical bone thickness. Determine the shape of the mandible. Settings and Design: A retrospective study was conducted using the CT scan images of pathologies pertaining to the Head and Neck region. Methods and Material: CT scan images of 30 patients, comprising of 22 males and 8 females. The mental foramen was considered as the anatomical landmark and the vertical marking was considered at a height of 20 mm from basal bone. The thickness of both cortical and cancellous bone was noted 6 mm anterior to it and 18 mm posterior. The shape of the buccal and lingual cortical bone was also considered. Statistical Analysis: Statistical analysis was done using Student's t-test or Chi-square test. Results: The mean thickness of cortical bone was more in anterior mandible than posterior mandible and cortical bone density was thickest at height of 20 mm, whereas for cancellous bone, it was highest at 5 mm from the basal bone, thickness. Buccal concavity, type A (68.2%), was the most common in the anterior region for males, followed by round shape, type C (56-58%) in the posterior region. For females, type C (25-31%) in the posterior region and lingual concavity, type B (18-30%) were the most common types in the anterior region. Conclusions: Lingual concavity may pose serious problems in cases of perforations during implant placement. Lingual cortical plates were thicker than the buccal cortical plates and it is concave anterior mandible. Thus, CT imaging can help in characterizing the quantity and morphology of the mandible.